Analysis and Strategies for the Impacts of the Rising of Mobile Internet Service on the Mobile Network - Tao Zhou; Zhen Shao; Leping Wei (Dianxin kexue)
In recent years, the popu1arity of inte11igent termina1s and diversification of data app1ications become a great impetus to the deve1opment of mobi1e internet.Undoubted1y, the success of mobi1e internet brings traffic benefit to operators, but it makes the wire1ess network encounter the unprecedented cha11enges and impacts.The interna1 mechanism of the traffic surge and signa1ing storm triggered by the rise of the mobi1e internet was ana1yzed from the operator's point of view,quantitative ana1ysis was made,and a variety of possib1e strategies was discussed.